COMPUTATIONAL STUDY OF IRON(II) SPIN TRANSITION COMPLEXES - T Male, Yusthinus
The change of two different spin electronic states under influence of temperature, pressure, light irradiation and magnetic field was known as spin transition phenomena. Spin transition (ST) exist on octahedrally complexes with intermediate ligand field. ST complexes were intesively investigated because they are highly potential candidates for electronic materials. Most of ST complexes consist of iron(II) core which are surrounded of bidentate diimin ligand with nitrogen atoms acting as electron donor. By experimental method, many new ST complexes has been produced but their properties could not be predicted before they were synthesized.